New potential for the Leitz Infinity Coordinate Measuring Machine - Sanz, Claude; Cherif, Ahmed; Mainaud-Durand, Hélène; Schneider, Jürgen; Steffens, Norbert; Morantz, Paul; Shore, Paul (euspen, 2015)
The following study is realised within the frame of the PACMAN project: a study on Particle Accelerator Components Metrology and Alignment to the Nanometre scale, which is a Marie Curie program supported by the European commission and hosted by CERN (European Organisation for Nuclear Research). The aim of this program is to develop and build a pre-alignment bench on which each component is aligned to the required level in one single step using a stretched wire. During the operation, the centre of the stretched wire is aligned with the magnetic axis of the magnet. Then, the position of the wire is measured to the highest possible accuracy using a 3D Coordinate Measuring Machine (CMM) Leitz PMM-C Infinity from HEXAGON Metrology. The research described in this paper is two-fold: on one hand we apply a strong magnetic field to the head of the CMM and evaluate its influence on the measurement accuracy; on the other hand we measure the position
Keywords: Metrology; Coordinate measuring machine; Magnetic measurements; Non-contact probing